Correlation between ISAMS and ATMOS measurements of CO in the middle atmosphere - Lopez-Valverde, M; Lopez-Puertas, M; Taylor, F; Gunson, MR (1999)
Measurements of IR emissions from CO at 4.6 mu m in the middle atmosphere were recorded for nearly one year, from September 1991 to July 1992 by the Improved Stratospheric and Mesospheric Sounder (ISAMS) on board the Upper Atmosphere Research Satellite (UARS). These have been used to retrieve carbon monoxide abundances and study their distribution and variability in the middle atmosphere. Observations of carbon monoxide in this atmospheric region and from transitions of the same vibrational-rotational band were also carried out, using the solar occultation technique with fine altitude resolution, by the high resolution interferometer ATMOS during the ATLAS-1 mission (late March and early April 1992). Comparisons between these simultaneous emission and absorption experiments have been performed in order to improve and validate both data sets. Some of the first results and conclusions are presented and discussed. (C) 1999 COSPAR. Published by Elsevier Science Ltd.